2015
DOI: 10.1007/s10439-015-1503-4
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial Mechanical Evaluation of Absorbable and Nonabsorbable Synthetic Surgical Meshes Used for Hernia Repair: Physiological Loads Modify Anisotropy Response

Abstract: The aim of this study was to obtain information about the mechanical properties of six meshes commonly used for hernia repair (Surgipro(®), Optilene(®), Infinit(®), DynaMesh(®), Ultrapro™ and TIGR(®)) by planar biaxial tests. Stress-stretch behavior and equibiaxial stiffness were evaluated, and the anisotropy was determined by testing. In particular, equibiaxial test (equal simultaneous loading in both directions) and biaxial test (half of the load in one direction following the Laplace law) were selected as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…1 Several studies have revealed that hernia treatment with mesh leads to a lower recurrence rate. 2 The advantages and disadvantages of different mesh materials have been evaluated to create modern polymeric meshes in a historical duration. 3 As a perfect prosthesis, the mesh should have crucial functional properties: safety, sterilization ability, biocompatibility, enough strength, suitable pore size, adequate porosity, structural stability, and good formability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Several studies have revealed that hernia treatment with mesh leads to a lower recurrence rate. 2 The advantages and disadvantages of different mesh materials have been evaluated to create modern polymeric meshes in a historical duration. 3 As a perfect prosthesis, the mesh should have crucial functional properties: safety, sterilization ability, biocompatibility, enough strength, suitable pore size, adequate porosity, structural stability, and good formability.…”
Section: Introductionmentioning
confidence: 99%
“…11 A surgical mesh’s mechanical response has to define because an anisotropic mesh’s random orientation can lead to inconsistent surgical outcomes. 2…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once implanted in the recipient wall, the incorporation with tissue lining should imitate the biomechanical properties of the healthy abdominal wall. Studies have shown that the permanence of the high-weight mesh causes persistent inflammatory reaction at the mesh-tissue interface for months, and even years after implantation 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have found that adult skeletal muscle has certain repair potential after injury. Studies have shown that the physiological repair process of skeletal muscle injury can be divided into three stages [3]: the first stage is the formation of hematoma at the site of muscle injury. In the second stage, the satellite cells around the injured muscle were activated, and the fibroblasts restored the connective tissue skeleton.…”
Section: Introductionmentioning
confidence: 99%